Thermal Performance Analysis of an Air-Based Hybrid PV/T Solar Collector in a Greenhouse under Varying Mass Flow Rates - Jimmy Richardo Ginting; Ayu Zahra Chandrasari; Ahmad Rajani (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Solar photovoltaic panels often experience electrical efficiency degradation due to heat accumulation, which can be effectively mitigated using hybrid photovoltaic/thermal (PV/T) systems. While a PV/T system concurrently generates electrical and thermal energy, the scope of this specific study is exclusively limited to evaluating its thermal performance and heat distribution. This study analyzes the thermal performance of an air-based hybrid PV/T solar collector integrated with a greenhouse. Because the system does not utilize phase change materials, the primary variable evaluated is the air mass flow rate, which is controlled by adjusting the number of active fans in both the PV/T collector and the greenhouse exhaust. Experimental data were collected over three days between 09:00 and 15:00 WIB. The testing was simplified into three operational scenarios: maximum PV/T - maximum greenhouse, maximum PV/T - minimum greenhouse, and minimum PV/T - minimum greenhouse. The numerical air velocities recorded were 3.70 m/s for the maximum PV/T setup and 2.35 m/s for the minimum. Concurrently, greenhouse exhaust velocities were 3.18 m/s (10 fans) and 2.03 m/s (6 fans). Findings revealed that the highest average useful heat reached 368.28 W during the maximum PV/T-minimum greenhouse scenario, highlighting optimal heat accumulation. Conversely, the highest average thermal efficiency was achieved in the maximum PV/T-maximum greenhouse scenario at 25.30%, demonstrating better air circulation and thermal stability. Ultimately, the results indicate that PV/T air velocity strongly governs heat extraction from the panels, whereas greenhouse exhaust velocity dictates heat retention inside the chamber.